Evaluation of hypermobile teeth deviation during impression taking in a partially edentulous dental arch: An in vitro study comparing digital and conventional impression techniques - Matsuno, Hitomi; Wada, Junichiro; Murakami, Natsuko; Takakusaki, Kensuke; Nagayama, Tomiharu; Manabe, Kaho; Nomura, Yugo; Koyama, Shinsuke; Mouri, Yuki; Li, Bin; Sakamoto, Kazuki; Kim, Eung-Yeol; et al. (JAPAN PROSTHODONTIC SOC, 2025)
Purpose: This study aimed to compare the deviation of hypermobile teeth in partially edentulous dental arches during impression taking using digital and conventional techniques.
Methods: A partially edentulous mandibular model with three target hypermobile teeth (including the left first premolar, #34; left second molar, #37; and right first premolar, #44), was used as the simulation model. After reference data were acquired using a desktop scanner, impressions of the simulation model were obtained using a digital intraoral scanner (IOS) and two conventional techniques (hydrocolloid material with a stock tray and silicone material with a custom tray as impression data (n=12/group). The three-dimensional accuracy (root mean square value) and two-dimensional accuracy (mesiodistal and buccolingual displacements) of the target teeth in each impression dataset were calculated based on the reference data. The comparison among three impression techniques was statistically performed using the Kruskal-Wallis test (α=0.05).
Results: For #34 and #44, the three- and two-dimensional accuracies of the impressions fabricated through data acquired through digital scanning (digital impression) were significantly superior to those of the hydrocolloid impression (P < 0.05), whereas no significant difference was found between the digital and silicone impressions. For #37, no significant difference in the accuracy of the impression data for the target teeth was observed among the three impression techniques.
Conclusions: Digital impression acquiring using an IOS is recommended over using a conventional hydrocolloid impression to prevent the deviation of hypermobile teeth in partially edentulous dental arches. Hypermobile tooth deviation in digital impression data depends on the tooth location.